Sharp three-dimensional notches under combined nominal normal and shear fatigue loading (Fracture and Structural Integrity, 2017)
Many engineering structures are exposed to non-proportional fatigue loading. However, at the critical location of crack initiation, often only one of the load sequences dominates – the individual load cases result in different crack initiation sites. Based on engineering judgment a simplified local uniaxial or proportional loading situation may be assessed. In general, the critical location must be identified by calculating fatigue lives for a variety of locations. The position of the critical location depends on the hypothesis applied for life calculation – besides loading, geometry, material and many other influence factors. For sharp three-dimensional notches the region for the search of the critical location may be restricted considerably. Weld start and stop points are an industrial example for such sharp notches. They are the object of the present investigation. They are exposed to nominal normal and shear loading. The individual hot spots for crack initiation lie necessarily close together. A strong interaction of the loading cases for both proportional and non-proportional loading was experimentally observed. In the numerical investigation notch stresses were calculated using an idealised weld end model. Based on the critical plane approach according to Findley, numerical interaction lines were produced.
Keywords: Combined loading; Multiaxial fatigue; Notch stress concept; Critical plane appraoch; Weld ends